Learning Difficulties and Coping Mechanisms of Education Students in the Shift to Flexible Learning Modality amidst COVID-19 Pandemic - Olila, Rowel (JPAIR Institutional Research, 2021)
Coping is a mental process that hopes to reduce or diminish stress. It may work on a conscious or unconscious level is determined by personality traits, personal characteristics, and resilience. Levels of adaptation are unique and can never be the same for two people. As educational institutions struggle to continue despite the ensuing COVID-19 Pandemic, online resources, learning management systems, synchronous and asynchronous teaching and learning modalities, blended and flexible learning, and a thousand different online applications and platforms were sought to facilitate the delivery of quality education still. The sudden shift to the new normal in education brought difficulties to students, teachers, administrators, and all education stakeholders. This quantitative research investigated the learning difficulties and coping mechanisms of 166 Education students of Aurora State College of Technology in the shift to flexible learning modality. The researcher used the questionnaire to identify the learning difficulties and the coping mechanisms of the respondents. The study utilized frequency count, percentage, and weighted mean. It is interesting to note that with the sudden shift to flexible learning modality, the respondents experience moderate difficulty as to Content (WM=3.0), performance tasks (WM=2.8), and summative tests (WM=2.9). Furthermore, concerning the experienced learning difficulties, respondents do cope-up with a medium amount (WM=3.3). That the most valuable coping strategies amidst the ensuing Pandemic are the following:  developing new learning styles and habits, utilization of technology that can aid learning, and committing oneself to discipline, commitment, and purpose.
Keywords: Education; learning difficulties; coping mechanisms; descriptive survey; Philippines